The complete mitochondrial genome of northern grasshopper mouse (Onychomys leucogaster) - Bi, Guiqi (Mitochondrial DNA B Resour, 2017)
In this study, we presented the complete mitochondrial genome of northern grasshopper mouse (Onychomys leucogaster). The circular genome is 16,370 bp in length and contains 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, 2 ribosome RNA genes, and 1 D-loop control regions. The overall nucleotide composition is: 31.2% A, 25.2% T, 29.9% C, and 13.6% G, with a total G + C content of 43.53%. The phylogenetic tree was constructed to validate the taxonomic status of Onychomys leucogaster, exhibiting a closest relationship with Neotoma fuscipes.